Integrating Social Literacy into Social and Cultural Diversity Lessons: A Case Study of Pancasila Education Textbooks for Grade IV Elementary Schools - Lutfiana Nurohmah; Unik Ambar Wati; Celine Widyaningrum Kusumawardani; Intan Purnama Dewi (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the indicators of social literacy embedded in the social and cultural diversity material within the Pancasila and Citizenship Education textbook for Grade IV of elementary schools (SD/MI), published by the Indonesian Ministry of Education and Culture. Social literacy is essential for fostering students’ awareness and appreciation of Indonesia’s diverse society. Using a qualitative descriptive approach, this study employed content analysis to examine the textbook. Data were collected through systematic reading and note-taking. The analysis followed six stages: data collection, sampling, recording, data reduction, conclusion drawing, and narrative construction. The findings reveal that the textbook integrates social literacy through its presentation of social and cultural diversity. The content not only introduces key social and cultural concepts but also encourages the development of interpersonal skills, such as communication, empathy, and openness to difference. These elements promote active engagement with diversity in everyday social contexts. The integration of social literacy within the textbook fosters a deeper student understanding of ethnic, religious, cultural, and linguistic diversity in Indonesia. This approach supports the formation of student character grounded in the values of tolerance, inclusivity, and national identity. By embedding these principles in Pancasila and Citizenship Education, the curriculum contributes to shaping responsible citizens who value plurality as a foundational aspect of Indonesian society.